The Impact of Arctic Amplification on Mid-latitude Winter Weather: An Analysis of the Stratospheric Pathway - Kappenberger, Franziska; Spiegl, Tobias; Langematz, Ulrike (Freie Universität Berlin, 2025)
The dataset includes climate model simulation output for three simulations with constant boundary conditions: pre-industrial (ts1850), present (ts2020) and future (ts2100). Data is provided on a regular 128×64 longitude-latitude grid covering the globe. Some datasets are available for the Northern Hemisphere only. Height-resolved data spans pressure levels from 1000 hPa to 0.01 hPa. This study explores the stratospheric pathway of the Arctic mid-latitude linkage (AML), a mechanism that connects Arctic amplification (AA) to cold winter weather in mid-latitudes. Using the chemistry-climate model EMAC, we investigate the transition of the AML signal between the troposphere and the stratosphere, focusing on changes in wave activity. Three timeslice experiments were analyzed, covering pre-industrial (1850), present (2020), and future (2100) climates. Compared to a pre-industrial state, both climate change simulations reveal increasing wave propagation and wave breaking in the stratosphere, accompanied by a higher occurrence of sudden stratospheric warmings (SSWs). This intensified wave activity enters the stratosphere particularly from the North Pacific and the Atlantic/European region. An evaluation of subseasonal wave activity episodes reveals more frequent tropopause-level wave input events during winter. While we found a significant rise in SSW events in our climate change simulations, their downward influence on mid-latitude winter weather appears to diminish, likely due to a warmer Arctic and the reduced severity of cold air outbreaks. Furthermore, we relate the changes in planetary wave generation to tropospheric baroclinicity, which is controlled by horizontal temperature gradients and static stability. Notably, AA suppresses baroclinic wave formation by weakening horizontal temperature gradients in the lower troposphere. In contrast, the enhanced wave generation in the mid-latitude upper troposphere could be attributed to temperature modifications at nearby altitudes, driven by tropical warming and ...